2012
DOI: 10.1097/bpo.0b013e318256117c
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Results of Late-relapsing Idiopathic Clubfoot Previously Treated With the Ponseti Method

Abstract: Therapeutic level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 19 publications
0
19
0
3
Order By: Relevance
“…They found a subsequent relapse after tibialis anterior tendon transfer in 15 % of feet (ten patients with 15 club feet) [72]. The results of the treatment of relapse were evaluated in another study and it was observed that at an average age at final follow-up of 23.3 years (range eight to 50.6 years) 90 % of patients wore regular shoes, 41 % had pain with activities, but only 18 % were limited in function by their feet [73].…”
Section: Results Of Treatmentmentioning
confidence: 99%
“…They found a subsequent relapse after tibialis anterior tendon transfer in 15 % of feet (ten patients with 15 club feet) [72]. The results of the treatment of relapse were evaluated in another study and it was observed that at an average age at final follow-up of 23.3 years (range eight to 50.6 years) 90 % of patients wore regular shoes, 41 % had pain with activities, but only 18 % were limited in function by their feet [73].…”
Section: Results Of Treatmentmentioning
confidence: 99%
“…Given its visual nature, with one or both feet turned inwards at birth, clubfoot can be a major source of uncertainty for the parents of the children affected after diagnosis and during treatment [5,11]. Uncertainty can also manifest because of the relapses that may occur after treatment [12-14]. Furthermore, available clubfoot treatment options vary and their efficacy depends on the experience of the health care provider [15-17].…”
Section: Introductionmentioning
confidence: 99%
“…However, some deformities remain resistant to conservative treatment, even for trained and specialized teams. Bad outcomes depend on multifactorial parameters [ 3 , 10 , 34 36 ].…”
Section: Discussionmentioning
confidence: 99%